Pengaruh Promosi Melalui Media Sosial TikTok dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Lozy Hijab - Auriel Putri Marlina; Halimah Zahrah (Indo Publishing, 2026)
The development of social media, particularly TikTok, has become an effective promotional tool in influencing consumer behavior in the digital era. According to Kotler and Keller, promotion is a marketing activity aimed at communicating product value to consumers, while consumer trust, as defined by Mowen and Minor, refers to consumers’ confidence in the reliability and integrity of a brand. This study aims to examine the influence of promotion through TikTok social media and consumer trust on purchasing decisions of Lozy Hijab products. This research employs a quantitative method, with data collected through questionnaires distributed to Lozy Hijab consumers who have been exposed to promotional content on TikTok. The data were analyzed using multiple linear regression analysis. The results indicate that promotion through TikTok social media has a positive and significant effect on purchasing decisions of Lozy Hijab. In addition, consumer trust also has a positive and significant effect on purchasing decisions. Simultaneously, promotion through TikTok social media and consumer trust have a significant influence on the purchasing decisions of Lozy Hijab.